Versilia: il paesaggio del turismo - Mariella Zoppi (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
The tourism in Versilia is identified in the fascist period when new horizons are be opened by the building of the motorway that links Florence with the seaside. This tourism is characterized by developing along the whole coast, from Carrara harbor to Viareggio town. It isn’t a new project but a landscape that opens to new uses, intercepting the phenomenon of Mass tourism that will characterize the XIX century.